Development and Validation of a Rapid RP HPLC Method for the Determination of Cinitapride Hydrogen Tartarate in Solid Oral Dosage Forms - Syeda Humaira; Akalanka Dey; S.Appala Raju; Syed Sanaullah (E-Journal of Chemistry)
In the present study a simple, sensitive rapid and accurate HPLC method with UV detection for the analysis of cinitapride hydrogen tartarate was developed and validated in solid dosage forms. The method utilized gradient elution technique with C18 column (150×4.6 mm I.D, 5 μm particle size) with mobile phase consisting of 0.1% formic acid in water and acetonitrile The detection wavelength was at 268 nm, with flow rate of 0.5 mL/min and injection volume of 10 μL for separation of cinitapride in bulk drugs and pharmaceutical formulations. The gradient elution was developed for better and optimized results. The developed method was validated for precision which includes system precision and method precision, accuracy and linearity studies in the concentration range of 5-100 μg/mL with correlation coefficient of 0.9987. The accuracy (recovery) was between 97.32 and 100.82%. The proposed method is simple, fast, accurate, precise and reproducible, hence can be applied for routine quality control analysis of cinitapride in pure and pharmaceutical dosage forms.